(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2022)
The purpose of this article is to analyse the possibility of using taxation as an instrument for sustainable development and consequently, as a form of state intervention in the pursuit of the fulfillment of the provisions of Article 170, section VI, of the Federal Constitution of Brazil. For this reason, the matter of development and state intervention in the economy is studied, with the aim of shaping the premises for the use of taxes as an instrument in the pursuit on sustainability. Finally, examples of the application of the institute are assessed in order to conclude for its viability.